AgNOR clusters as a parameter of cell kinetics in chronic lymphocytic leukaemia. Issue 6 (December 1996) - Lorand-Metze, Irene; Metze, Konradin
Abstract : Aims —To study correlations between the pattern of silver stained nucleolar organiser regions (AgNORs) in chronic lymphocytic leukaemia (CLL) and parameters of tumour kinetics. To investigate whether quantitation of the AgNOR pattern can be used to discriminate between patients with stable and progressive disease. Methods —Peripheral blood smears from 48 patients with CLL, classified as having either stable or progressive disease (Rai stage III or IV; bulky lymph nodes or massive splenomegaly; or peripheral lymphocytes >100 × 10 9 /1), were studied. For each patient, total tumour mass (TTM) and for patients undergoing a period of observation without treatment, the TTM duplication time (DT) and the lymphocyte doubling time (LDT) were calculated. Results —Four cell types could be distinguished according to their AgNOR pattern: (1) cells with a single cluster; (2) cells with a single compact nucleolus; (3) cells with two compact nucleoli; and (4) cells with several scattered dots. The percentage of cells with clusters was the AgNOR parameter which correlated best with TTM and LDT. Correlations were also seen between the proportion of cells with clusters and age and haemoglobin concentration. A significant correlation with DT could be detected only when age was kept constant. Linear discriminant analysis revealed that the percentage of cells with clusters was the most important prognostic factor. This alone classified 94% of the patients correctly (jackknive procedure) as either stable or progressive CLL. Conclusions —The percentage of circulating lymphocytes with clusters of AgNORs can be used as a parameter of tumour kinetics in CLL and helps to discriminate between patients with stable and progressive disease. For practical purposes, a value of more than 13% of cells with clusters is suggestive of progressive disease.